Owners of the Map : Motorcycle Taxi Drivers, Mobility, and Politics in Bangkok - Sopranzetti, Claudio (Book collections on Project MUSE., 2017)
"On May 19, 2010, the Royal Thai Army deployed tanks, snipers, and war weapons to disperse the thousands of Red Shirts protesters who had taken over the commercial center of Bangkok to demand democratic elections and an end to inequality. Key to this mobilization were motorcycle taxi drivers, who slowed down, filtered, and severed mobility in the area, claiming a prominent role in national politics and ownership over the city and challenging state hegemony. Four years later, on May 20, 2014, the same army general who directed the dispersal staged a military coup, unopposed by protesters. How could state power have been so fragile and open to challenge in 2010 and yet so seemingly sturdy only four years later? How could protesters who had once fearlessly resisted military attacks now remain silent? Owners of the Map provides answers to these questions--central to contemporary political mobilizations around the globe--through an ethnographic study of motorcycle taxi drivers in Bangkok. Claudio Sopranzetti explores the unresolved tensions in the drivers' everyday lives, their migration trajectories, consumer desires, and political demands amidst the restructuring of Thai capitalism after the 1997 economic crisis. Reconstructing the entanglements between their everyday mobility and political mobilization, Sopranzetti reveals mobility not just as a strength of contemporary capitalism but also as one of its fragile spots, always prone to disruption by the people who sustain its channels but remain excluded from their benefits. In so doing, Owners of the Map advances an analysis of power that focuses not on the sturdiness of hegemony or the ubiquity of everyday resistance but on its potential fragility as well as the work needed for its maintenance."--Provided by publisher.